1991
DOI: 10.1111/j.1749-6632.1991.tb24442.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Asbestos Fibers in Lung Parenchyma, Pleural Plaques, and Mesothelioma Tissues of North American Insulation Workersa

Abstract: Asbestos fibers and ferruginous bodies (FBs) in lung parenchyma, lung cancer tissues, pleural plaques, and pleural and peritoneal mesothelioma tissues from 13 North American insulation workers were analyzed and quantified using an analytical transmission electron microscope and a polarized microscope. Diseases from which these workers suffered included asbestosis, lung cancer, and mesothelioma. They had been occupationally exposed to materials containing chrysotile and amosite; their pathological diagnoses, oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 13 publications
1
109
0
3
Order By: Relevance
“…This translocation also probably occurs in humans since asbestos fibers have been detected in human pleural lesions. (36) However, the mechanism and route of translocation are unclear. It has been suggested that penetration through the visceral pleura, possibly driven by increased pulmonary interstitial pressure and assisted by enhanced permeability of the visceral pleura due to asbestosinduced inflammation might be a major route.…”
Section: Discussionmentioning
confidence: 99%
“…This translocation also probably occurs in humans since asbestos fibers have been detected in human pleural lesions. (36) However, the mechanism and route of translocation are unclear. It has been suggested that penetration through the visceral pleura, possibly driven by increased pulmonary interstitial pressure and assisted by enhanced permeability of the visceral pleura due to asbestosinduced inflammation might be a major route.…”
Section: Discussionmentioning
confidence: 99%
“…Heller [63] found asbestos fiber burdens ranging from 56,738 to 1,963,250 fibers per gram wet weight tissue in the tumor tissue among six of seven women with peritoneal mesothelioma. Kohyama et al [72] looked for asbestos fibers and ferruginous bodies (iron coated asbestos fibers) in lung parenchyma, lung cancer tissues, pleural plaques, and pleural and peritoneal mesothelioma tissues from thirteen North American insulation workers; fibers were found in extrapulmonary sites. Amosite fibers were fewer in number in both pleural plaques and pleural and peritoneal mesothelioma tissues than in lung tissue, whereas chrysotile fibers were seen in similar numbers as in the lungs.…”
Section: Experimental Datamentioning
confidence: 99%
“…Given the possibility of a post-depositional movement of chrysotile fibers from the lung to the pleura [43][44][45][46][47][48], such statements are an over simplification. The rate of asbestos retention cannot be characterized only on the basis of measurements of fiber contents in pulmonary tissues -The proportion of chrysotile fibers (as opposed to the amphiboles) was shown to be higher in parietal pleura than in lung tissue [43].…”
Section: Page -02mentioning
confidence: 99%
“…Moreover, the accelerated clearance of chrysotile from the lung can be partly caused by a disintegration of chrysotile (but not amphibole) fibers into thin fibrils, which are more difficult to identify. The total number of fibrils would increase due to fiber splitting [47,49,50], possibly together with the carcinogenic effect, as the split fibrils can move to the pleura [45,47,48]. Asbestos fibers have been identified in the pleura by autopsy, chrysotile being the predominant asbestos form found in pleural plaques [51] and pleural/mesothelial tissues in general [46,52].…”
Section: Page -02mentioning
confidence: 99%
See 1 more Smart Citation